Online updating Bsc thesis abstract / Kamariah Kamal - Kamariah, Kamal (2004)
Information Retrieval is the study of systems for indexing, searching, and recalling data, particularly text or other unstructured forms. With the implementation of Information Retrieval techniques on Internet searching are more efficient and effective. This project is aimed at creating an on-line updating facility for BSc students to update their thesis abstracts. A template is provided for the student to fill-up. A template consists of name of student, student ID, year of project, supervisor name, title of project and thesis abstract. Student must fill-up their abstract after get their result. It is implemented on-line so that fixture students and lecturers can view the abstract more easily. Efficiency, effectiveness, and accuracy of updating information are important.